Pengaruh Biaya Produksi, Biaya Operasional dan Volume Penjualan Terhadap Kinerja Keuangan pada CV. Salim Media Indonesia Periode 2021-2023 - Perdana Putra Elpian; Mellya Embun Baining; Achyat Budianto; Marnas Nazir (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to reveal the effect of production costs, operational costs and sales volume on financial performance at CV. Salim Media Indonesia for the 2021-2023 period. This thesis uses a quantitative approach using the multiple regression statistical analysis method partially and simultaneously with 35 samples. The results of the study indicate that production costs have an effect on financial performance at CV. Salim Media Indonesia for the 2021-2023 period partially. Operational costs have an effect on financial performance at CV. Salim Media Indonesia for the 2021-2023 period partially. Sales volume has an effect on financial performance at CV. Salim Media Indonesia for the 2021-2023 period partially. Based on the calculated F value > F table and the significant value < a , it is concluded that Ho is rejected and Ha is accepted, meaning that Production Costs and Operational Costs together or simultaneously have an effect on financial performance at CV. Salim Media Indonesia for the 2021-2023 period.